An Assessment of Cryptomixing Services in Online Illicit Markets - Holt, Thomas J. (Journal of contemporary criminal justice, 2023)
The internet has become a popular marketplace for the sale of illicit products, including stolen personal information, drugs, and firearms. Many of these products are acquired using cryptocurrencies, which are generally defined as forms of digital currency that is traceable through blockchain ledger technology. These currencies are thought to be more secure than other forms of digital payment, though law enforcement and financial service providers have found ways to investigate account holders and their transactions. Consequently, several service providers have begun to offer cryptomixing services, which effectively launders payments to circumvent detection and investigation tools. Few have explored the practices of cryptomixing services, or the ways in which they are marketed on the Open and Dark Web. This inductive qualitative analysis will examine a sample of 18 cryptomixing services advertised on both the Open and Dark Web to better understand cryptomixing and its role in facilitating illicit transactions across the internet.